Role of FcRγ and factor XIIIA in coated platelet formation - Jobe, Shawn M. (© 2005 by The American Society of Hematology, 2005)
Platelet activation in response to dual stimulation with collagen and thrombin results in the formation of a subpopulation of activated platelets known as coated platelets. Coated platelets are characterized by high surface levels of α-granule proteins and phosphatidylserine, which support the assembly of procoagulant protein complexes. Using murine models, we tested the hypothesis that the collagen receptor-associated molecule FcRγ and the transglutaminase factor XIIIA are required for the formation of coated platelets. Following dual stimulation with the collagen receptor agonist convulxin and thrombin, 68% of platelets from C57BL/6 mice acquired the coated platelet phenotype, defined by high surface levels of fibrinogen and von Willebrand factor and decreased binding of the αIIbβ3 activation-dependent antibody PE-JON/A. In FcRγ(-/-) mice, only 10% of platelets became “coated” after dual stimulation with convulxin plus thrombin (P < .05 vs C57BL/6 platelets). Decreased coated platelet formation in FcRγ(-/-) platelets was accompanied by decreased annexin V binding (P < .01) and decreased platelet procoagulant activity (P < .05). Platelets from FXIIIA(-/-) mice did not differ from control platelets in coated platelet formation or annexin V binding. We conclude that FcRγ, but not factor XIIIA, is essential for formation of highly procoagulant coated platelets following dual stimulation with collagen and thrombin.